Tindak Lanjut Evaluasi Mahasiswa Terhadap Dosen (Studi Kasus Universitas Airlangga) - Jeffits Khusnu Alif (Jurusan Akuntansi Politeknik Negeri Malang, 2019)
This research focuses on the status of the lecturer as the foundation of a University , because the have the responsibility to educating a new generation that could bring pride to University, so there is no doubt that lecturer could be called the most valuable asset of the University (Ramírez Córcoles, Santos Peñalver, & Tejada Ponce, 2011; Suyunus, 2011; Ulum, 2012). This research is a case study research with intepretif paradigm, which aim to determine the extent to which the result of a student evaluation of lecturer that measured by Airlangga University cybercampus questionnaires used as references by it’s lecturer and faculty. Abstrak Penelitian ini berfokus pada status dosen sebagai fondasi dari sebuah Universitas, karena bertanggung jawab mendidik generasi baru yang dapat mengharumkan nama Universitas, sehingga tidak heran apabila dosen disebut sebagai aset paling berharga dari Universitas (Ramírez Córcoles et al., 2011; Suyunus, 2011; Ulum, 2012). Penelitian ini adalah penelitian studi kasus berparadigma intepretif, yang bertujuan untuk mengetahui sejauh mana hasil dari penilaian mahasiswa terhadap kinerja dosen yang diukur dengan kuisioner cybercampus Universitas Airlangga dijadikan acuan oleh dosen dan fakultas.